«Muerte al Estado» y la lucha en el territorio de los cuerpos - Meo Laos, Verónica Gabriela (2022)
The following text takes as its axis of analysis a demonstration held in Mexico City on March 8, 2020, when 80 000 women gathered to commemorate International Women’s Day. Prior to the march that departed from the Monument to the Revolution, feminist collectives gathered on the plancha of the capital’s Zócalo, at 10 am, to paint in white letters the names of the victims of femicide since 2016. Three days later, the global health context changed completely, because the quarantine that banned circulation in public space and confined the world’s population to the private sphere began. Prior to that, in the midst of the multitudinous convocation, Mexican journalist Amaranta Atxín Marentes photographed a brunette woman with black hair, dressed only in tattered red pants, a green jacket and with her torso painted red, posing in front of a street graffiti that, next to a symbol of anarchy, read “Death to the State”. Based on the photograph taken by Marentes, this article proposes to analyze the context of production and reception from semiotics and intersectionality in order to reflect on the relationship between the State, identity, and the political participation of “third world” women and, at the same time, as a way of avoiding oblivion.